Bibliometric Analysis of Hybrid Learning During Covid-19 in Physics Learning - Della Anggelia; Eko Risdianto (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2023)
This research aims to understand student perspectives and the most appropriate and effective learning approaches during the combined online and face-to-face learning period. The research method used is analyzing literature using bibliometric techniques which begins by defining the keyword 'Hybrid Learning' in the Publish or Perish application with Google Scholar as the data source. After reducing the scope of the search by focusing on specific aspects of 'hybrid learning', a total of 19 relevant articles were selected from a total of 50 articles found in the initial stage of the search. The collected data is managed using the Mendeley application, while the Vosviewer application is used to produce visualizations of related research. The research results show that physics learning became more effective when the Covid-19 virus outbreak broke out by implementing a hybrid approach, which helped improve students' technology skills. However, continued use of this approach in schools can have negative consequences for students. So, it can be concluded that hybrid learning is effective in physics learning when the Covid-19 virus is spreading. Because hybrid learning can improve students' abilities in using technology. However, it can also have a negative impact on students if it is applied continuously at school.